Factors Associated With Inability to Bear Weight Following Hip Fracture Surgery: An Analysis of the ACS-NSQIP Hip Fracture Procedure Targeted Database. (25th April 2019) - Malik, Azeem Tariq; Quatman-Yates, Catherine; Phieffer, Laura S.; Ly, Thuan V.; Khan, Safdar N.; Quatman, Carmen E.
Introduction: While the benefits of early mobility for prevention of complications such as pneumonia, thromboembolic events, and improved mortality have been well studied in postsurgical patients, it is unclear which patients may struggle to achieve full weight-bearing on the first postoperative day. Materials and Methods: The 2016 American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) Targeted Hip Fracture Database was queried regarding the ability to achieve weight-bearing on first postoperative day for older adults. Cases that occurred secondary to malignancy were excluded or for which weight-bearing was unachievable on the first postoperative day due to medical reasons were excluded. Results: A total of 6404 patients met inclusion and exclusion criteria for the study, with 1640 (25.6%) patients unable to bear weight on the first postoperative day. Following adjusted analysis, nonmodifiable patient factors such as dependent (partial or total) functional health status, dyspnea with moderate exertion (odds ratio [OR]: 1.31 [95% confidence interval, CI: 1.04-1.65]), ventilator dependency, and preoperative dementia on presentation to hospital were associated with lack of achievement of weight-bearing on the first postoperative day. Modifiable patient factors such as presence of systemic inflammatory response syndrome (OR: 1.35 [95% CI: 1.11-1.64]), delirium, and low preoperative hematocrit and modifiable system factors including delayed time to surgery, total postoperative time >90 minutes, and transfer from an outside emergency department were also associated with inability to achieve weight-bearing on the first postoperative day. Discussion: Medical teams can utilize the results from this study to better identify patients preoperatively who may be at risk of not achieving early mobilization and proactively employ implement strategies to encourage mobility as soon as possible for hip fracture patients.